Pengembangan E-Sport dan Industri Gaming Menggunakan Analisis SWOT - Achmad Gunawan; Ahmad Hidayatullah; Abdurrahim Hidayat (CV. Syntax Corporation Indonesia, 2021)
This aim of the study is describing the opportunities and challenges of developing the esports and gaming industry, as a qulitative analysis using secondary data. The analysis uses the SWOT method and then submits suggestions to address these opportunities and challenges as policy recommendations. The results are: (1) esports and the gaming industry are two different things, the realm of the gaming industry is very broad and difficult to identify only in the context of its relation to esports. (2) the challenges that exist are more related to the values ​​that are relatively shifting between generations in line with technological developments. (4) the opportunity is very big for both the esports and the gaming industry, for the gaming industry a strong economic policy structure must be built that can maximize the potential for prosperity without hindering the development of esports and the gaming industry itself. (5) The policy for esports is to align esports with other sports, which is currently being carried out by the Ministry of Youth and Sports and other sports institutions.